“MBUJANG” DANCE WORK IN DRAMATIC FORM AS A VISUALIZATION OF THE PROCESS OF SELF DISCOVERY - Musthofa, Adam musthofa; Dwi Sasanadjati, Jajuk (Solah, 2025)
Abstract: The Mbujang dance work is a dramatic visualization of teenagers’ search for identity through reflection on the choreographer’s empirical experiences. The character of Bujang Ganong in Reyog Ponorogo art is used as a basis for exploring movements to describe the emotional and social dynamics experienced by teenagers in the process of growing up. The purpose of this work is to present a symbolic representation of the journey of adolescents in finding their identity. The creation method uses Jacqueline Smith’s Construction I, which includes the stages of initial stimulus, dance type, presentation mode, improvisation, evaluation, selection, and motif discovery. These stages are applied systematically to produce a complete choreography. The result of this creation is embodied in the dramatic dance work Mbujang, which combines the distinctive movements of Bujang Ganong with contemporary processing. This work depicts the struggles of teenagers between anxiety, social interaction, and the effort to find balance within themselves. Elements of tradition and modernity are combined through movement, music, and artistic design, resulting in a new expression that is contextual to the lives of today’s teenagers. The work Mbujang is expected to enrich the repertoire of dramatic dance art as well as serve as a reflection for individuals to understand the importance of the process of searching for one’s identity. Keywords: Dramatic dance, search for identity, youth, Bujang Ganong, Mbujang